Reasons to counterfeit: Supply, demandand distribution of counterfeit goods - Mussanova, Aneliya (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This research empathizes with the opportunities that drive demand for counterfeit goods. Governments, organizations and rights holders struggle to regulate the distribution and consumption of counterfeit products, so that consumer awareness has emerged as to what goods people counterfeit, and most importantly, why people intentionally buy counterfeit items. This article illustrates the incentives that inspire buyers to purchase counterfeit products, tactics that brand owners use to fueltheir interest. It involves the development of demand, marketing tactics, and the implementation of consumer approach strategies by brands. It also reveals the complicated logistics and transporting routes creating manufacturing and transit hubs for counterfeiting; it also demonstrates the lack of government intervention as well as the desperate need for policy revision. This article shows counterfeiting is phenomenon that governments, organizations, and most importantly, consumers all have equal interest in fighting against.
Keywords: consumer goods; copyright; intellectual property rights; international copyrights; international trade